Binary Higher Education System In The Republic Of Croatia With Emphasize On The Professional Higher Education - Halak, Željka Vajda; Romić, Danijela (European Scientific Journal, ESJ, 2016)
In the Republic of Croatia, higher education is performed through university and professional studies. University studies are performed at universities and professional studies are performed at polytechnics and schools of professional higher education primarily, but they can be performed at universities also, with the prior consent by National Council for Higher Education. Professional study has two levels which are professional study that last two to three years and specialist professional graduate study that last one to two years. There are currently 104 public higher education institutions, 11 of them are polytechnics and 3 are schools of professional higher education. Also there are 28 private higher education institution, 4 of them are polytechnics and 22 are schools of professional higher education. It is interesting to mention the fact from Central Bureau of Statistics in the Republic of Croatia, according to which, in the academic year 2014/15 enrolled 157,827 students from which the largest number of students were enrolled in university studies (68,97%). Here can be raised the legitimate question why there is so much difference between professional and university studies in the registered number of students and whether the reasons can be found in a lack of awareness of students or the unattractive study programs. The aim of this paper is to show the binary higher education system, kinds of professional studies in the Republic of Croatia and the possible reasons that students still prefer to choose a university study for their education.